To Form in the Minds of Students Studying in Higher Education Methods of Working with the Songs of Talqin and Nasr from the 1st Group Branches of Shashmaqom - Khuraliyeva Marifatkhon (Research Parks Publishing LLC, 2021)
The maqoms, which embody the history of the Uzbek people in magical tones, are one of the most developed types of musical creation, which is mainly created and performed in a monodic style. Each maqom has its own clear text, that is, it is performed with a ghazal. They mainly used ghazals and muhammas of classical poets such as Lutfi, Atoyi, Navoi, Babur, Fuzuli, Avaz Otar, Ogahi.